Effects of Interior Color Schemes on Emotion, Task Performance, and Heart Rate in Immersive Virtual Environments. Issue 4 (9th August 2020) - Cha, Seung Hyun; Zhang, Shaojie; Kim, Tae Wan
ABSTRACT: The purpose of this study was to investigate the effects of interior color schemes in immersive virtual environments (IVEs) on emotion, task performance, and heart rate to examine IVEs' potential for interior color research. Fifty‐five ( n = 55) student participants were recruited to experience four different colored IVE models (i.e., red, green, blue, and white), and their emotions, heart rate change, and proofreading performances during the immersion were measured. Participants were also asked about their sense of presence after the experience. The findings support the following three hypotheses: (1) IVE interior color schemes affect subject emotion, (2) IVE interior color schemes affect subject task performance as measured through a proofreading exercise, and (3) IVE interior color schemes affect subject heart rate. Specifically, red was perceived as significantly heavier, warmer, more exciting, tenser, and unpleasant. Significantly fewer errors occurred during the white immersion versus the green color scheme when completing the task performance exercise. While heart rate was reduced for each color, significant decreases were detected in the blue, white, and green color scenarios. The majority of participants felt a sense of being there when experiencing the four colored IVE spaces. Based on these results, we conclude that IVE has potential for interior color research to overcome the limitations of traditional color research tools.